Current Situation and Teaching and Learning Management of the General Music Curriculum at the University in Inner Mongolia, China - Zheng, Xiaolu; Rungsuk, Anong; Phromphithakkul, Wasin (วารสารวิชาการ การจัดการภาครัฐและเอกชน, 2023)
The objectives of this research were: 1) to study attitudes and satisfaction towards teaching and learning music for undergraduate students at the university level in Inner Mongolia area. 2) To study the current conditions and desirable teaching and learning management in music subjects for undergraduate students at the university level in Inner Mongolia area. 3) To study the strengths, weaknesses, opportunities and threats in the management of music teaching for undergraduate students at the university level in Inner Mongolia area. The population consisted of 1039 students enrolled in music courses and 31 general music teachers from 17 universities in Inner Mongolia. The research tools were Mean, Standard Deviation (SD) and Priority Need Index (PNImodified). The results showed that 1) The instructor (teacher) was most satisfied with the music teaching arrangement. 2) The highest attitude towards the policy “14th Five-Year Educational Development Plan in Inner Mongolia Autonomous Region” was concrete and practical behavior. The highest attitude towards the educational learning management process was control in determining the roles and responsibilities of those responsible for supervising, monitoring, inspecting, and evaluating the workload. 3) The current conditions toward Classroom Management: 8 Strategic Current and Desirable Conditions of Teaching and Learning Management and Classroom Management: 8 Strategic overall, it was at the moderate level, and the desirable condition, overall, it was at the highest level. 4) Order of Needs and Necessities was Reporting, Planning, Budgeting, Create an Effective Learning Environment, Create A Motivational Environment and Establish Classroom Procedures. 5) The strengths were Keep Everyone Engaged and Create a Motivational Environment. The weaknesses were Establish Classroom Procedures and Create an Effective Learning Environment. The opportunities were Directing and Staffing. The threats were Reporting and Planning.